INTERAKSI KOMUNIKASI BERBASIS MEDIA PEMBELAJARAN DALAM PROSES BELAJAR-MENGAJAR - Azhar Azhar; Syukur Kholil; Soiman Soiman (Edukasi Islami : Jurnal Pendidikan Islam, 2015)
Interaction of communication in the learning process is an attempt to hold educational interaction in the learning activities, so that learning objectives can be achieved effectively and efficiently. Communication is the process of learning educational rapport between teachers and students which built effective communication and influence each other in a state of feeling between them in order to provide an opportunity for students to achieve the expected. Several methods of learning communication interaction that can be used to develop educational learning behavior in a variety of events interaction. To set the method of interaction where appropriate, the teacher should first establish whether a method can be said to be good, there needs to reference that originates in the primary factor which determined that "goal" to be achieved. To overcome the barriers in the communication process of learning required a variety of tools and/or media that can serve as the means used to distribute messages. In classroom learning, facilities or amenities tool used to facilitate communication with the media learning called learning. Kata kunci: Interaksi, Komunikasi, Pembelajaran.